2020
DOI: 10.1172/jci129205
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of multiple myeloma

Abstract: had markedly impaired IFN-γ production, although this phenotype was reversible (13). Together, these studies indicate that T cell-dependent myeloma immunity is present, albeit suppressed, in patients with myeloma.NK cells play a key role in myeloma immunity, and NK dysfunction has been implicated in myeloma progression in nontransplanted myeloma-bearing mice (42). MGUS patients were found to have similar or increased numbers of NK cells compared with healthy donors, while patients with late-stage myeloma have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 174 publications
(228 reference statements)
0
138
0
2
Order By: Relevance
“…A recent study suggested that the development of mutation-specific KRAS inhibitors could be of great value in patients with KRAS -mutant PCM [ 32 , 33 ]. Moreover, results of the correlation between RAS/RAF mutations and complex karyotypes suggested the therapeutic benefit of checkpoint inhibitors in this group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the development of mutation-specific KRAS inhibitors could be of great value in patients with KRAS -mutant PCM [ 32 , 33 ]. Moreover, results of the correlation between RAS/RAF mutations and complex karyotypes suggested the therapeutic benefit of checkpoint inhibitors in this group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this phase, resistant tumor cells acquire genetic and epigenetic alterations that eventually lead to escape the immune recognition, allowing for uncontrolled proliferation and clinical progression (escape) ( 19 21 ). A potential application of this model in MM identifies in the MGUS/SMM precursor stages a phase of immune equilibrium ( 22 ). In this context, marked heterogeneity of MM cells, along with constitutive and ongoing genomic instability, and modulations occurring in the composition of the BM milieu may underlie immune escape and disruption of the immune equilibrium during disease progression ( 22 ).…”
Section: Immune Dysfunction and Tumor Immune Evasion Mechanismsmentioning
confidence: 99%
“…A potential application of this model in MM identifies in the MGUS/SMM precursor stages a phase of immune equilibrium ( 22 ). In this context, marked heterogeneity of MM cells, along with constitutive and ongoing genomic instability, and modulations occurring in the composition of the BM milieu may underlie immune escape and disruption of the immune equilibrium during disease progression ( 22 ). Specifically, the strict and symbiotic interaction between MM cells and the BM microenvironment facilitate tumor immune escape via several mechanisms: immunosuppressive cells in the BM; disruption of antigen presentation by downregulating major histocompatibility complex and/or costimulatory molecules; loss or mutation of cancer-specific antigens; and upregulation of decoy receptors or complement inhibitory receptors ( 5 , 23 ).…”
Section: Immune Dysfunction and Tumor Immune Evasion Mechanismsmentioning
confidence: 99%
“…Immune dysregulation retains a crucial role in the pathogenesis and disease progression of multiple myeloma (MM), since genetic lesions per se are necessary but not sufficient to the progression from monoclonal gammopathy of undetermined significance (MGUS) to overt MM [ 1 , 2 ]. Several factors including T cell exhaustion, tolerance induction by tumor associated microenvironment, cytokines production alteration and increase in myeloid-derived suppressor cells (MDSCs), and tumor-associated macrophages with suppressive properties contribute in the neoplastic escape form immune surveillance, ultimately leading to disease progression [ 3 , 4 , 5 , 6 ]. Allogenic stem cell transplantation is traditionally regarded as the first immunotherapeutic strategy and the only curative option for many hematological malignancies.…”
Section: Immunotherapy In Multiple Myelomamentioning
confidence: 99%